Features of activity of persons with the lacks of mental development in Kherson separation of invasport - Stepanyuk S.; Lomaka Z.; Bazhanova V. (Kharkov National Pedagogical University, 2010)
The origin of physical culture and sport is analysed among persons with the lacks of mental development in the world and Ukraine. The specific of development of athletic-sporting motion of environments is investigational inferior with the lacks of mental development in Kherson. The prospects of further development of sport of persons are outlined with the lacks of mental development in Kherson. Material is presented about achievements of Kherson sportsmen-invalids with the lacks of mental development on international competitions. Study and popularization of sport inferior is an important factor for development of sporting practice.